Firm Size, Corporate Social Responsibility, and Tax Avoidance: Evidence from the Consumer Non-Cyclicals Sector in Indonesia - Dwi Septiani; Ferdiansyah (LPPM Universitas Pekalongan, 2025)
This study investigates the influence of firm size and corporate social responsibility (CSR) on tax avoidance among companies in Indonesia's consumer non-cyclicals sector, a subject gaining importance amid growing scrutiny of corporate tax practices. Integrating agency theory and legitimacy theory, the research aims to understand how external oversight and the pursuit of social legitimacy shape tax behavior, particularly in a context that remains underexplored in Indonesia. Utilizing a quantitative approach, the study analyzes panel data from 30 companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. Tax avoidance is proxied by the effective tax rate (ETR), CSR is measured using a GRI-based disclosure index, and firm size is assessed through the natural logarithm of total assets. Multiple linear regression was employed following model selection and classical assumption testing. The findings reveal that CSR has a significant negative effect on tax avoidance, whereas firm size does not exhibit a partial effect. However, both variables jointly influence tax avoidance significantly. These results underscore the role of CSR in promoting ethical corporate behavior and suggest that regulators and stakeholders should actively encourage CSR initiatives to enhance tax compliance and corporate transparency.